PENGERING SUMBER ENERGI BIOMASSA SABUT KELAPA MENINGKATKAN PENGHASILAN PERAJIN IKAN TERI SKALA RUMAH TANGGA - I Gede Bawa Susana; Ida Bagus Alit (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The process of drying anchovy traditionally causes the temperature and drying time to be suboptimal. This affects the income of anchovy fish processing workers. To increase the income of anchovy processing workers, a dryer is designed with a coconut fiber biomass energy source. The study was conducted on a sample of 20 people and a drying chamber capacity of 24 kg of wet anchovy. The drying process is carried out in the drying chamber. The drying chamber is integrated with a coconut fiber biomass burning stove and heat exchanger. Hot air drying is obtained through the conversion of coconut fiber thermal energy. The process of energy conversion occurs between the burning of coconut fiber in the furnace with environmental air flowing in the heat exchanger pipe. The resulting hot air flows into the drying chamber. This system has an impact on weather-free drying. In addition, the results of drying become hygienic. This has implications for the increased income of anchovy processing workers. Profits reach 3,408,000.00 IDR every month. Anchovy processing workers enjoy the profit from the investment costs of the dryer after 4.464 months. Coconut fiber biomass dryer has a Return on Investment level of 274.36%. It can be said that the application of coconut fiber biomass dryers in the process of drying anchovies provides positive results in the form of economics the profits.